Corporate governance and firm performance: evidence from India. - Poudel, Ramji (Cranfield University, 2019)
Corporate governance (CG) has attracted much public interest in the last three decades because of its apparent importance for the financial health of corporations, for the economy, and society in general. Most prior studies have focussed on CG issues in developed economies, particularly in the USA, UK, and other European countries, arguing that the advanced economies have relatively resolved their CG problems. CG issues are rooted in the separation of ownership and control of corporations with widely diffused ownership structures and managerial controls that result in agency problems between owners and managers. CG models of these advanced economies have been branded as the international benchmark for the best practices. Emerging economies are rising to become global economic superpowers. Many of them are newly liberalized, but in a short period, they have been overtaking advanced economies in terms of sizes and growth rates. CG problems in emerging economies are manifest via the concentration of ownership, prevalence of family control, and pyramidal ownership structures having entirely different institutional contexts for CG structures. However, little is known about the impact of CG on firm performance in emerging and developing economies. To understand the evolving perspective of CG in emerging economies, I look at India. This thesis is organized in paper format with three journal papers. Paper 1 describes the evolving perspective of CG in India. Its first part analyses the evolution of CG in India in three stages: the managing agency model (in the colonial period until 1947); the conglomerates or business house model (1947-1991); and the Anglo-American model (after 1991). My analysis shows that the modern form of CG in India evolved with the economic liberalization of 1991. Since then it has gone through several reform processes with well structured CG laws, regulations and codes, such as Clause 49 of the Listing Agreements, the Corporate Governance Voluntary Guidelines 2009, the Companies Act 2013, and the Insolvency and Bankruptcy Code of India 2016. These CG laws, guidelines and codes are intended to provide a strong CG environment in the country, so that it can resolve CG problems and strengthen the financial health of corporations. The second part of the paper compares CG systems in India with those of the USA and UK in six areas, i.e. CG regulatory frameworks, board structures and committees, ownership structures, stakeholder relationships, financial accounting, auditing and reporting practices, and markets for finance. Initially, the CG systems in India were closer to the UK’s business-based CG model of ‘comply or explain’, but after the Companies Act 2013, Indian CG systems moved closer to the US regulations-based CG model of ‘comply or die’. Paper 2 discusses how performance indicators, such as Tobin’s Q, returns on assets (ROA) and returns on equity (ROE), are affected by a company’s leadership styles, and by it’s board’s size, independence, compensation, and gender diversity, plus it’s directors’ age, tenure, activities, and external commitments. From a sample of around 150 large Indian companies for five years from 2010/11 to 2014/15, listed on Bombay Stock Exchange (BSE) and National Stock Exchange (NSE), I construct a panel data, and I use system-generalized methods of moments (system GMM) on fixed effects regression models. The regression results show that board independence has a negative association with all performance indicators because of the lack of unified and prudent decisions. Directors’ tenure positively affects Tobin’s Q and ROA, implying that long- serving directors are good stewards of firms’ resources. CEO duality negatively affects Tobin’s Q, suggesting that the concentration of both the decision-making role and supervisory role in a single individual does not improve firm performance. Boardroom gender diversity is negative with ROA and ROE, which implies that companies appoint women directors as tokens to comply with the laws. Board size, external commitments, compensation and activities have no significant association with performance indicators. Past performance, as measured by one year lag of performance variables, are positive with the current year’s performance, implying that there is a dynamic effect on firm performance. In Paper 3, I empirically examine the components of ownership structure, as the key elements of internal governance mechanisms of the companies. Components of ownership structure, such as institutional ownership, promoter groups’ ownership, proportions of promoter directors, blockholders’ dispersion, family control, directors’ property, and government ownership are examined by linking them with firm performance, Tobin’s Q, ROA and ROE. In an unbalanced panel data of 150 large Indian companies, I use system GMM estimation on fixed effects regression models. I find that equity ownership of institutional investors has a positive impact on Tobin’s Q, indicating that institutional investors are independent, and they do not compromise as monitors of the firm. Family control improves firms’ accounting performances, as indicated by positive associations between family control and ROA and ROE. These results suggest that family control lowers agency problems between owners and managers and also does not adversely affect the interests of minority shareholders. Family members in family-controlled firms act as stewards instead of agents, and their behaviour improves firm performance. Similarly, ownership by promoter or promoter groups’ positively affects market performance as measured by Tobin’s Q. Higher percentage of ownership gives the promoters enough incentive and control to monitor managerial activities. Non-executive directors’ (NEDs) ownership has a negative association with ROA and ROE. NEDs, who hold a nominal proportion of ownership stake of the firms, are neither active directors nor fully independent, which can damage firm performance. Blockholders’ dispersion has a positive relationship with Tobin’s Q and negative association with ROA and ROE. These results suggest that markets react positively to the presence of multiple blockholders; however, multiple blockholders are damaging accounting performance due to the presence of a new set of conflicts among blockholders, and between large blockholders and minority shareholders. Government ownership of companies has no significant association with performance measures.
Keywords: Corporate governance; board of directors; ownership structure; India; US; UK; Tobin's Q; ROA; ROE